Pengembangan E-Modul Biologi Berbasis Indigenous Knowledge Suku Dayak Kenyah pada Materi Inovasi Teknologi Biologi - Nanda, Muhammad Arya; Turista, Dora Dayu Rahma; Akhmad, Akhmad; Kurniawati, Zenia Lutfi (Biocaster : Jurnal Kajian Biologi, 2025)
The use of technology in education has encouraged innovation in teaching materials, one of which is the development of Indigenous Knowledge-based E-Modules to align knowledge with the surrounding culture and environment. This study aims to develop and assess the feasibility of a Biology E-Module based on Indigenous Knowledge of the Dayak Kenyah Tribe on the subject of Biology Technology Innovation at SMA IT Granada Samarinda. The type of research used is Research and Development (R&D) with the 4D model (Define, Design, Develop, and Disseminate) which in this study was carried out up to the Develop stage. The research subjects included one Biology teacher, 23 students of class XA1 at SMA IT Granada Samarinda, and five Dayak Kenyah cultural informants in Pampang Cultural Village. Data collection instruments were in the form of interviews, questionnaires, and validation sheets which were analyzed qualitatively and quantitatively. The validation results showed the feasibility of the E-Module from the material aspect of 91% and media 82%. Student responses in small group and large group trials reached 80.50% and 85.21%, respectively, which were categorized as very feasible. The findings indicate that integrating Indigenous Knowledge into E-Modules supports more contextual and engaging Biology learning. This study recommends further exploration of the potential of local knowledge as an innovative resource in the development of digital learning media.